2004
DOI: 10.4161/cbt.3.2.611
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Survivin-Derived CTL Epitopes with Different HLA-A-Restriction Profiles

Abstract: The identification of tumor antigens, which are essential for the survival of tumor cells is a new avenue to prevent antigen loss variants emerging due to immunoselection, particularly during immune therapy. In the search for such immunogenic tumor antigens, we recently identified spontaneous cytotoxic lymphocyte (CTL) responses against the inhibitor of apoptosis protein survivin. Thus, we identified two HLA-A2-restricted, survivin-derived CTL epitopes, which both were targets for spontaneous CTL responses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 41 publications
2
50
0
2
Order By: Relevance
“…This will lead to more specific survivin vaccines that would elicit better immune response, generate immune memory and offer protection from tumor progression [44] . The development of antibodies is still costing a large amount of money and there are several considerations for their use [19,45] .…”
Section: Immune Response Against Survivinmentioning
confidence: 99%
See 1 more Smart Citation
“…This will lead to more specific survivin vaccines that would elicit better immune response, generate immune memory and offer protection from tumor progression [44] . The development of antibodies is still costing a large amount of money and there are several considerations for their use [19,45] .…”
Section: Immune Response Against Survivinmentioning
confidence: 99%
“…Survivin is a tumor-associated antigen so it could be a potential target for immunotherapy [34] . During the search for immunogenic tumor antigens, spontaneous CTL responses against survivin were identified [45] . Survivin is an attractive target for vaccination since immune escape by down regulation or loss of expression of this protein would impair sustained tumor growth.…”
Section: Immune Response Against Survivinmentioning
confidence: 99%
“…The availability of multiple survivin epitopes presented by different HLA restriction elements further reduces the risk of immune escape and thereby might improve therapeutic effectiveness. While several survivin-derived CTL epitopes are known in humans [19,20,31,32], there are only limited reports for the murine system [27,33].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of multiple survivin epitopes presented by different HLA restriction elements further reduces the risk of immune escape and thereby might improve therapeutic effectiveness. While several survivin-derived CTL epitopes are known in humans [19,20,31,32], there are only limited reports for the murine system [27,33].In the present study, we identified two H-2K were carried out as described [36]. The assembly assay is based on stabilization of the class I molecule after loading of peptide to the peptide transporter-deficient cell line RMA-S.…”
mentioning
confidence: 99%
“…47 Another 'shared' antigens is survivin, a member of the inhibitor of apoptosis protein family. 48,49 Survivin is an inhibitor of the effector caspases 3 and 7 resulting in blockade of the mutual downstream events of both the death-receptormediated and mitochondrial apoptosis pathways. 50 Association with early events in leukemogenesis is documented in patients with myelodysplastic syndrome (MDS) by an increase in survivin expression prior to development of overt leukemia.…”
Section: Dc-based Leukemia Vaccinesmentioning
confidence: 99%